Orientalism, occidentalism and the sociology of crime - Cain, Maureen E. (The British journal of criminology, 2000)
This paper builds upon my experience of teaching criminology at the University of the West Indies in Trinidad, where it emerged over an eight-year period that the issues which were most salient in that context might not be covered at all in western criminology texts, and that the theoretical presumptions of western criminology were as likely to be misleading, or at best to miss the point, as to be helpful. An analysis of these difficulties revealed the twin failings in western criminology of orientalism, which romanticizes the other, and occidentalism, which denies the possibility of difference, or seeks to explain it away. The deep presumptions of western theories may be harmful for non-western consumers of them. Meanwhile, western criminology inhibits its own theoretical development by limiting its theorization of difference to resistance. Consideration of an issue relevant to but located outside criminology, that of violence against women and children, reveals the possibility of an interactive globalization in which people living in different societies may more constructively learn from each other